2021
DOI: 10.1177/1729881421989551
|View full text |Cite
|
Sign up to set email alerts
|

Flight planning in multi-unmanned aerial vehicle systems: Nonconvex polygon area decomposition and trajectory assignment

Abstract: Nowadays, it is quite common to have one unmanned aerial vehicle (UAV) working on a task but having a team of UAVs is still rare. One of the problems that prevent us from using teams of UAVs more frequently is flight planning. In this work, we present the first open-source solution ( https://pypi.org/project/pode/ ) for splitting any complex area into multiple parts. The area of interest can be convex or nonconvex and can include any number of no-flight zones. Four solutions, based on the algorithm of Hert and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…This algorithm is based on the most compact partition of a polygon into two parts. The performance and the quality of the obtained results were compared against an algorithm described in [20] and [33], and against an approach with brute-force search over a discretized polygon border. It was shown that the algorithm presented in this paper is more efficient and the resulting parts show much better quality in terms of compactness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This algorithm is based on the most compact partition of a polygon into two parts. The performance and the quality of the obtained results were compared against an algorithm described in [20] and [33], and against an approach with brute-force search over a discretized polygon border. It was shown that the algorithm presented in this paper is more efficient and the resulting parts show much better quality in terms of compactness.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we show the quality of the results obtained with our algorithm compared against two different approaches. The first approach is the algorithm from [20] implemented in [33]. The second approach is a naive approach.…”
Section: E Countersegment Parallel To Y-axismentioning
confidence: 99%
See 3 more Smart Citations